Crop rotation phase has a greater impact on soil biology than crop rotation diversity - Marijke Struijk; Erika Degani; Samuel G. Leigh; Emma Bowen; Sion Thomas; Simon R. Mortimer; Andrew P. Whitmore; Frank Ashwood; Suzanne J. Clark; Tom Sizmur (Agriculture, Ecosystems & Environment, 2026)

The effectiveness of microwave heating as an ISRU extraction technique on different arrangements of icy lunar regolith - James D. Cole; Simon Sheridan; Sungwoo Lim; Hannah M. Sargeant; Mahesh Anand; Hannah Chinnery; James Mortimer; Andrew Morse (Planetary and Space Science, 2025)

Absence of low-δ18O magmas despite widespread assimilation of altered crust in a large magmatic and hydrothermal province - Shane M. Rooyakkers; Isabelle Chambefort; Kevin Faure; Colin J.N. Wilson; Simon J. Barker; Nick Mortimer; Hannah C. Elms; Juliana Troch; Bruce L.A. Charlier; Graham S. Leonard; David Farsky (Geochimica et Cosmochimica Acta, 2023)

Absence of a home-field advantage within a short-rotation arable cropping system - Marijke Struijk; Andrew P. Whitmore; Simon Mortimer; Xin Shu; Tom Sizmur (Plant and Soil, 2023)
Aims The home-field advantage (HFA) hypothesis predicts faster decomposition of plant residues in home soil compared to soils with different plants ( away ), and has been demonstrated in forest and grassland ecosystems. It remains unclear if this legacy effect applies to crop residue decomposition in arable crop rotations. Such knowledge could improve our understanding of decomposition dynamics in arable soils and may allow optimisation of crop residue amendments in arable systems by cleverly combining crop-residue rotations with crop rotations to increase the amount of residue-derived C persisting in soil. Methods We tested the HFA hypothesis in a reciprocal transplant experiment with mesh bags containing wheat and oilseed rape residues in soils at three stages of a short-rotation cropping system. Subsets of mesh bags were retrieved monthly for six months to determine residue decomposition rates, concomitantly measuring soil available N, microbial community structure (phospholipid fatty acid analysis), and microbial activity (Tea Bag Index protocol) to assess how plants may influence litter decomposition rates via alterations to soil biochemical properties and microbial communities. Results The residues decomposed at similar rates at all rotational stages. Thorough data investigation using several statistical approaches revealed no HFA within the crop rotation. Soil microbial community structures were similar at all rotational stages. Conclusions We attribute the absence of an HFA to the shortness of the rotation and soil disturbance involved in intensive agricultural practices. It is therefore unlikely that appreciable benefits could be obtained in short conventionally managed arable rotations by introducing a crop-residue rotation.

Single introductions of soil biota and plants generate long‐term legacies in soil and plant community assembly - E. R. Jasper Wubs; Wim H. van der Putten; Simon R. Mortimer; Gerard W. Korthals; Henk Duyts; Roel Wagenaar; T. Martijn Bezemer (Ecology Letters, 2019)
Recent demonstrations of the role of plant–soil biota interactions have challenged the conventional view that vegetation changes are mainly driven by changing abiotic conditions. However, while this concept has been validated under natural conditions, our understanding of the long‐term consequences of plant–soil interactions for above‐belowground community assembly is restricted to mathematical and conceptual model projections. Here, we demonstrate experimentally that one‐time additions of soil biota and plant seeds alter soil‐borne nematode and plant community composition in semi‐natural grassland for 20 years. Over time, aboveground and belowground community composition became increasingly correlated, suggesting an increasing connectedness of soil biota and plants. We conclude that the initial composition of not only plant communities, but also soil communities has a long‐lasting impact on the trajectory of community assembly.

Legacy effects of grassland management on soil carbon to depth - Susan E. Ward; Simon M. Smart; Helen Quirk; Jerry R. B. Tallowin; Simon R. Mortimer; Robert S. Shiel; Andrew Wilby; Richard D. Bardgett (Global Change Biology, 2016)
The importance of managing land to optimize carbon sequestration for climate change mitigation is widely recognized, with grasslands being identified as having the potential to sequester additional carbon. However, most soil carbon inventories only consider surface soils, and most large‐scale surveys group ecosystems into broad habitats without considering management intensity. Consequently, little is known about the quantity of deep soil carbon and its sensitivity to management. From a nationwide survey of grassland soils to 1 m depth, we show that carbon in grassland soils is vulnerable to management and that these management effects can be detected to considerable depth down the soil profile, albeit at decreasing significance with depth. Carbon concentrations in soil decreased as management intensity increased, but greatest soil carbon stocks (accounting for bulk density differences), were at intermediate levels of management. Our study also highlights the considerable amounts of carbon in subsurface soil below 30 cm, which is missed by standard carbon inventories. We estimate grassland soil carbon in Great Britain to be 2097 Tg C to a depth of 1 m, with ~60% of this carbon being below 30 cm. Total stocks of soil carbon (t ha −1 ) to 1 m depth were 10.7% greater at intermediate relative to intensive management, which equates to 10.1 t ha −1 in surface soils (0–30 cm), and 13.7 t ha −1 in soils from 30 to 100 cm depth. Our findings highlight the existence of substantial carbon stocks at depth in grassland soils that are sensitive to management. This is of high relevance globally, given the extent of land cover and large stocks of carbon held in temperate managed grasslands. Our findings have implications for the future management of grasslands for carbon storage and climate mitigation, and for global carbon models which do not currently account for changes in soil carbon to depth with management.

Intensive agriculture reduces soil biodiversity across Europe - Maria A. Tsiafouli; Elisa Thébault; Stefanos P. Sgardelis; Peter C. de Ruiter; Wim H. van der Putten; Klaus Birkhofer; Lia Hemerik; Franciska T. de Vries; Richard D. Bardgett; Mark Vincent Brady; Lisa Bjornlund; Helene Bracht Jørgensen; et al. (Global Change Biology, 2015)
Soil biodiversity plays a key role in regulating the processes that underpin the delivery of ecosystem goods and services in terrestrial ecosystems. Agricultural intensification is known to change the diversity of individual groups of soil biota, but less is known about how intensification affects biodiversity of the soil food web as a whole, and whether or not these effects may be generalized across regions. We examined biodiversity in soil food webs from grasslands, extensive, and intensive rotations in four agricultural regions across Europe: in Sweden, the UK , the Czech Republic and Greece. Effects of land‐use intensity were quantified based on structure and diversity among functional groups in the soil food web, as well as on community‐weighted mean body mass of soil fauna. We also elucidate land‐use intensity effects on diversity of taxonomic units within taxonomic groups of soil fauna. We found that between regions soil food web diversity measures were variable, but that increasing land‐use intensity caused highly consistent responses. In particular, land‐use intensification reduced the complexity in the soil food webs, as well as the community‐weighted mean body mass of soil fauna. In all regions across Europe, species richness of earthworms, Collembolans, and oribatid mites was negatively affected by increased land‐use intensity. The taxonomic distinctness, which is a measure of taxonomic relatedness of species in a community that is independent of species richness, was also reduced by land‐use intensification. We conclude that intensive agriculture reduces soil biodiversity, making soil food webs less diverse and composed of smaller bodied organisms. Land‐use intensification results in fewer functional groups of soil biota with fewer and taxonomically more closely related species. We discuss how these changes in soil biodiversity due to land‐use intensification may threaten the functioning of soil in agricultural production systems.

Abiotic drivers and plant traits explain landscape‐scale patterns in soil microbial communities - Franciska T. de Vries; Pete Manning; Jerry R. B. Tallowin; Simon R. Mortimer; Emma S. Pilgrim; Kathryn A. Harrison; Phil J. Hobbs; Helen Quirk; Bill Shipley; Johannes H. C. Cornelissen; Jens Kattge; Richard D. Bardgett (Ecology Letters, 2012)
The controls on aboveground community composition and diversity have been extensively studied, but our understanding of the drivers of belowground microbial communities is relatively lacking, despite their importance for ecosystem functioning. In this study, we fitted statistical models to explain landscape‐scale variation in soil microbial community composition using data from 180 sites covering a broad range of grassland types, soil and climatic conditions in England. We found that variation in soil microbial communities was explained by abiotic factors like climate, pH and soil properties. Biotic factors, namely community‐weighted means (CWM) of plant functional traits, also explained variation in soil microbial communities. In particular, more bacterial‐dominated microbial communities were associated with exploitative plant traits versus fungal‐dominated communities with resource‐conservative traits, showing that plant functional traits and soil microbial communities are closely related at the landscape scale.

Influences of space, soil, nematodes and plants on microbial community composition of chalk grassland soils - Etienne Yergeau; T. Martijn Bezemer; Katarina Hedlund; Simon R. Mortimer; George A. Kowalchuk; Wim H. Van Der Putten (Environmental Microbiology, 2010)
Summary Microbial communities respond to a variety of environmental factors related to resources (e.g. plant and soil organic matter), habitat (e.g. soil characteristics) and predation (e.g. nematodes, protozoa and viruses). However, the relative contribution of these factors on microbial community composition is poorly understood. Here, we sampled soils from 30 chalk grassland fields located in three different chalk hill ridges of Southern England, using a spatially explicit sampling scheme. We assessed microbial communities via phospholipid fatty acid (PLFA) analyses and PCR‐denaturing gradient gel electrophoresis (DGGE) and measured soil characteristics, as well as nematode and plant community composition. The relative influences of space, soil, vegetation and nematodes on soil microorganisms were contrasted using variation partitioning and path analysis. Results indicate that soil characteristics and plant community composition, representing habitat and resources, shape soil microbial community composition, whereas the influence of nematodes, a potential predation factor, appears to be relatively small. Spatial variation in microbial community structure was detected at broad (between fields) and fine (within fields) scales, suggesting that microbial communities exhibit biogeographic patterns at different scales. Although our analysis included several relevant explanatory data sets, a large part of the variation in microbial communities remained unexplained (up to 92% in some analyses). However, in several analyses, significant parts of the variation in microbial community structure could be explained. The results of this study contribute to our understanding of the relative importance of different environmental and spatial factors in driving the composition of soil‐borne microbial communities.

Summer drought alters plant‐mediated competition between foliar‐ and root‐feeding insects - JOANNA T. STALEY; SIMON R. MORTIMER; MICHAEL D. MORECROFT; VALERIE K. BROWN; GREGORY J. MASTERS (Global Change Biology, 2007)
Summer droughts are predicted to increase in severity and frequency in the United Kingdom, due to climate change. Few studies have addressed the impacts of drought on interactions between species, and the majority have focussed on increases in CO 2 concentration and changes in temperature. Here, the effect of experimental summer drought on the strength of the plant‐mediated interaction between leaf‐mining Stephensia brunnichella larvae and root‐chewing Agriotes larvae was investigated. Agriotes larvae reduced the abundance and performance of S. brunnichella feeding on a mutual host plant, Clinopodium vulgare , as well as the rate of parasitism of the leaf‐miner. The interaction did not, however, occur on plants subjected to a severe drought treatment, which were reduced in size. Changes to summer rainfall, due to climate change, may therefore reduce the occurrence of plant‐mediated interactions between insect herbivores.

COMMENTARY ON KLEIJN ET AL . 2006 - Simon G. Potts; Richard B. Bradbury; Simon R. Mortimer; Ben A. Woodcock (Ecology Letters, 2006)

Community Associations of Chalk Grassland Leafhoppers (Hemiptera: Auchenorrhyncha): Conclusions for Habitat Conservation - Norbert Maczey; Greg J. Masters; John A. Hollier; Simon R. Mortimer; Valerie K. Brown (Journal of Insect Conservation, 2005)

Species divergence and trait convergence in experimental plant community assembly - Tadashi Fukami; T. Martijn Bezemer; Simon R. Mortimer; Wim H. van der Putten (Ecology Letters, 2005)
Despite decades of research, it remains controversial whether ecological communities converge towards a common structure determined by environmental conditions irrespective of assembly history. Here, we show experimentally that the answer depends on the level of community organization considered. In a 9‐year grassland experiment, we manipulated initial plant composition on abandoned arable land and subsequently allowed natural colonization. Initial compositional variation caused plant communities to remain divergent in species identities, even though these same communities converged strongly in species traits. This contrast between species divergence and trait convergence could not be explained by dispersal limitation or community neutrality alone. Our results show that the simultaneous operation of trait‐based assembly rules and species‐level priority effects drives community assembly, making it both deterministic and historically contingent, but at different levels of community organization.